Adult dietary protein has age‐ and context‐dependent effects on male post‐copulatory performance. (12th May 2017) - Macartney, E. L.; Crean, A. J.; Bonduriansky, R.
Abstract: The highly conserved effect of dietary protein restriction on lifespan and ageing is observed in both sexes and across a vast range of taxa. This extension of lifespan is frequently accompanied by a reduction in female fecundity, and it has been hypothesized that individuals may reallocate resources away from reproduction and into somatic maintenance. However, effects of dietary protein restriction on male reproduction are less consistent, suggesting that these effects may depend on other environmental parameters. Using the neriid fly, Telostylinus angusticollis, we examined age‐specific effects of adult dietary protein restriction on male post‐copulatory reproductive performance (fecundity and offspring viability). To explore the context dependence of these effects, we simultaneously manipulated male larval diet and adult mating history. We found that protein‐restricted males sired less viable offspring at young ages, but offspring viability increased with paternal age and eventually exceeded that of fully fed males. The number of eggs laid by females was not affected by male dietary protein, whereas egg hatching success was subject to a complex interaction of male adult diet, age, larval diet and mating history. These findings suggest that effects of protein restriction on male reproduction are highly context dependent and cannot be explained by a simple reallocation of resources from reproduction to somatic maintenance. Rather, these effects appear to involve changes in the scheduling of male reproductive investment with age.